ANALISIS PENILAIAN PROSES UNTUK ANAK BERKEBUTUHAN KHUSUS (ABK) PADA PEMBELAJARAN MATEMATIKA DI SD IT PERMATA - Layli Ila Ramadhani; Nur Khosiah; Yulina Fadilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of process assessment for children with special needs (ABK) in mathematics learning at Permata IT Elementary School. The study focuses on the application of authentic assessment strategies that emphasize not only final results but also stages of thinking, levels of participation, and the development of students' cognitive and affective abilities. This study used a qualitative approach, with data collection techniques including observation, teacher interviews, and analysis of assessment documents. The results indicate that process assessment provides a more comprehensive picture of the learning outcomes of children with special needs because it highlights individual development according to each child's characteristics. Teachers play a central role in designing and implementing adaptive and flexible assessment instruments to suit students' learning needs. Furthermore, the implementation of process assessment has been shown to support a more inclusive, participatory, and humane learning environment. The implications of this study demonstrate the importance of improving teacher competency in developing process-based assessment instruments, as well as the need for school institutional support in providing facilities and infrastructure that support learning oriented toward holistic student development.